2009
DOI: 10.1002/dvdy.22032
|View full text |Cite
|
Sign up to set email alerts
|

Conditional gene inactivation reveals roles for Fgf10 and Fgfr2 in establishing a normal pattern of epithelial branching in the mouse lung

Abstract: Fibroblast growth factor 10 (FGF10) signaling through FGF receptor 2 (FGFR2) is required for lung initiation. While studies indicate that Fgf10 and Fgfr2 are also important at later stages of lung development, their roles in early branching events remain unclear. We addressed this question through conditional inactivation of both genes in mouse subsequent to lung initiation. Inactivation of Fgf10 in lung mesenchyme resulted in smaller lobes with a reduced number of branches. Inactivation of Fgfr2 in lung epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
143
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 49 publications
16
143
4
Order By: Relevance
“…5C vs. B, G vs. F, J). This phenotype is similar to that obtained by Abler et al who used a general mesenchymal driver line (Dermo1 Cre ) to perform conditional gene inactivation of Fgf10 [14]. Last but not least, our research group has previously demonstrated that the gut is a major site of Fgf10 expression and that hypomorphic Fgf10 embryos (Fgf10 LacZ/2 ) suffered from cecal atresia [4].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…5C vs. B, G vs. F, J). This phenotype is similar to that obtained by Abler et al who used a general mesenchymal driver line (Dermo1 Cre ) to perform conditional gene inactivation of Fgf10 [14]. Last but not least, our research group has previously demonstrated that the gut is a major site of Fgf10 expression and that hypomorphic Fgf10 embryos (Fgf10 LacZ/2 ) suffered from cecal atresia [4].…”
Section: Discussionsupporting
confidence: 87%
“…Tomato flox/flox reporter mice (B6;129S6-Gt(ROSA)26Sor tm9(CAGtdTomato)Hze /J) [13] were purchased from Jackson lab and Fgf10 flox/flox mice [14,15] were a kind gift from Professor Suzanne L. Mansour (University of Utah, USA). Embryonic day 0.5 (E0.5) was assigned to the day when a vaginal plug was detected.…”
Section: Mice and Tamoxifen Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing the hypothesis that FGF10 is a master-regulator for lung development will require both the targeted deletion of its receptor in specific progenitor cell populations and a full analysis of the gene regulatory network controlling progenitor proliferation and morphogenesis. A lung epithelial-specific deletion of Fgfr2 has been performed and the results are consistent with roles in branching, survival, and proliferation (Abler et al, 2009). As yet, there has been no attempt to build a gene regulatory network for lung morphogenesis.…”
Section: Lung Progenitors and Branching Morphogenesismentioning
confidence: 74%
“…The lungs were cultured on E13, and, at that point, adriamycin-exposed embryonal organs were already smaller and less branched than controls. Their development remained impaired until the end of the experiment, and it is significant that Fgf10, a key mesenchymal regulator of the process of endodermal branching (19)(20)(21)(22) whose expression is delayed in mouse embryos exposed to adriamycin (23), was also downregulated in rats with EA-TEF at the end of gestation.…”
Section: Discussionmentioning
confidence: 99%